A intervenção precoce e o processo de inclusão educacional na educação infantil: ações e concepções de professores de educação especial - kaufmann, Jaqueline Daise (2021)
This research was developed within the scope of the Graduate Program in Education at the Federal University of Santa Maria, in the Special Education Research Line, inclusion, and difference and linked to the Study and Research Group in Education Psychology and Inclusive Education – GEPEIN. In this study, we sought to investigate how the practice of Early Intervention contributes to the inclusion of children with special educational needs in the context of Early Childhood Education. The Historical-Cultural perspective (VIGOTSKI, 1896-1934) and the Bioecological Systemic Model (BRONFENBRENNER, 1996; 2011) were used as a theoretical basis. In the first moment of the study, a mapping of scientific productions on the theme Early Intervention through the state of knowledge was carried out (MOROSINI and FERNANDES, 2014). After analyzing the knowledge production and the interviews carried out, we observed the lack of academic work related to Early Intervention related to Early Childhood Education and Special Education. We evidenced that most of the analyzed productions brings a predominance of practices focusing on the disability of children with rehabilitative bias, which reinforces the scarcity of research with an educational emphasis. Studies in this field are still beginners and require greater investment. In the second moment, we sought to reflect on the Early Intervention practice of Special Education teachers working in Early Childhood Education. For this, the research was developed with four Special Education teacher working in Early Childhood Education in the municipality of Santa Maria-RS. It has chosen a qualitative methodological approach. Data were collected through narrative interviews and analyzed using Bardin's Content Analysis (2011). In the conception of Special Education teachers, we found that they admit the need for the constant search for knowledge about practices that help the processes of school inclusion. The results indicate the recognition of Special Education teachers about the need for support regarding the practice of Early Intervention, which corroborates the importance of investments in initial and continuing training on the theme to act in the context of Early Childhood Education. The investigation also reveals the lack of inclusion policies in early childhood on the national scene, which indicates the need for articulation and strengthening of intentional actions to empower families in the context of intervention.